The Link Between 15-F2t-Isoprostane Activity and Acute Bovine Endothelial Inflammation Remains Elusive - Putman, Ashley K.; Sordillo, Lorraine M.; Contreras, G. Andres (Frontiers in Veterinary Science, 2022)
Modern dairy cattle suffer from increased incidence and severity of mastitis during major physiological transitions of the lactation cycle. Oxidative stress, a condition resulting from inadequate antioxidant defense against reactive oxygen and nitrogen species, is a major underlying component of mastitis pathophysiology. Isoprostanes (IsoP) are molecules derived from cellular lipid membranes upon nonenzymatic interaction with reactive species during inflammation, and are regarded as highly sensitive and specific biomarkers of oxidative stress. Changes in IsoP concentrations have been noted during major physiological transitions and diseases such as coliform mastitis in dairy cattle. However, the biological role of IsoP during oxidative stress in dairy cows has not been well-elucidated. Therefore, this study aimed to characterize the impacts of IsoP on oxidative stress outcomes in a bovine model of acute endothelial inflammation. Bovine aortic endothelial cells (BAEC; n=4) were stimulated with 2,2'-azobis (2-amidinopropane) dihydrochloride (AAPH) or lipopolysaccharide (LPS) with or without 15-F2t-IsoP to determine how IsoP influence oxidative stress outcomes. Our endothelial inflammation model showed relatively decreased reactive metabolites and increased barrier integrity in cells treated with both the agonist and IsoP compared to agonist treatment alone. However, IsoP do not appear to affect oxidative stress outcomes during acute inflammation. Understanding the effect of IsoP on BAEC is an early step in elucidating how IsoP impact dairy cows during times of oxidative stress in the context of acute clinical mastitis. Future studies should define the optimal dosing and treatment timing of IsoP to maximize their cytoprotective potential during acute inflammation.